Patients' experiences of their healthcare in relation to their expectations and satisfaction: a population survey. (April 2013) - Bowling, Ann; Rowe, Gene; Mckee, Martin
Objectives: To investigate patients' experiences of health services, and how these related to what they had expected to receive, and satisfaction with their care. Design: Surveys of patients before and after their consultations in general practice and hospital outpatients departments. Setting: Greater London and Essex Participants: In total, 833 patients attending 21 hospitals (434 patients; 52%) and 22 general practices (399 patients; 49%) across Greater London and Essex sampled in clinics and a population survey. Main outcome measures: Patient expectations of care, patient satisfaction. Results: Compared with younger people, and those in black and ethnic minority groups, older people (aged 65+) and White British people had significantly higher overall realistic expectations of their care (pre-visit realistic expectations score: age 60+: mean 53.26 [standard deviation 13.73]; age <60: 56.20 [15.17]; White British: 54.41 [13.50]; Black and other ethnic groups: 56.90 [16.15]) and greater satisfaction post-consultation (satisfaction score age 60+: 1.71 [0.80]; age <60: 1.97 [0.97]; White British: 1.79 [0.89]; Black and other ethnic groups: 2.01 [0.95]). Pre-visit ideal and realistic expectations of care was not significantly associated with patient satisfaction, although met expectations (post-visit experiences) were. Elements of these which was predictive of satisfaction were communication with the doctor, information conveyed and clinical outcomes. Factors associated with satisfaction included having a sense of control over one's life, being older, female, White British and attending general practice, compared with hospital outpatient clinics. Conclusions: It is the ability of the system to meet patients' expectations in respect of the emotional and human features of the consultation, and the clinical outcomes, that matter most to people. This research also questions prevailing stereotypes of older age: it is not the case that older patients are more satisfied with their care because their expectations are lower. In fact, they are higher, but they believe that they are being met.